The Exploration of the Surrounding Nature Approach with the Discovery Learning Model for Biology Learning Outcomes - Triana Kartika Santi (Jurnal Penelitian Pendidikan IPA, 2023)
The learning activities to be realized are meaningful learning for the lives of students. Learning that can be applied to help students get to know the surrounding environment as an object of science is the exploration of surrounding nature. This study aims to determine the effect of the surrounding nature approach with the Discovery Learning model on biology learning outcomes for class X SMA Banyuwangi. This research is a Quasi-Experimental Design. The sample was selected using a simple random sampling technique which had previously been tested using a homogeneity test. The sample in this study was class X IPA 1 as the experimental class, and class X IPA 2 as the control class. Data analysis using the ttest formula. The results of data analysis obtained tcount = 7.369 greater than the ttable value Î± 5% = 1.672, so it can be concluded that there is an influence of the surrounding nature approach with the Discovery Learning model on biology learning outcomes for class X SMA Banyuwangi. The discovery learning model really helps students to gain direct learning experience so that the understanding students get in learning will enter long-term memory and not easily be forgotten.